(untitled) (Indian Journal of Arid Horticulture, 2025)
The objective of this study was to determine the effect of GA3 and cow urine on seed germination and seedling growth of custard apple. The results of the present study showed significant differences with respect to the effect of seed soaking in different concentrations of GA3 (200, 400, 600 ppm) and cow urine with 15% and 20%, as well as in combination. Seeds were soaked for 72 hours in all treatments. The results revealed the positive effect of GA3 alone and in combination with cow urine on germination percentage, seedling growth, seedling diameter, number of leaves, and vigour index. Among the various treatments, GA3 (400 ppm) in combination with cow urine (15%) exhibited the highest germination percentage (92.40%), whereas the lowest germination was observed in the control group (50.07%). However, GA3 alone also had a positive effect on germination and seedling growth.